Pelatihan Dokumentasi, Story Telling, Dan Branding Ekowisata Kepada Pokdarwis Desa Paau Kecamatan Aranio Kabupaten Banjar - Fahrianoor Fahrianoor; Muhammad Nizar Hidayat (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Ecotourism is one of the main streams in Indonesia's tourism program. One area that has great ecotourism potential is South Kalimantan Province, especially in Paau Village, Aranio District, Banjar Regency. One of the problems found is the low quality of local Pokdarwis as tourism stakeholders, especially in the use of online media for ecotourism promotion. For this reason, the community service program this time is directed at strengthening the ability to master Pokdarwis online information media by conducting documentation training, storytelling, and branding the ecotourism potential of Paau Village. The approach used in this partnership program is an approach based on partner needs and program assistance activities by first identifying problems and then proceeding with developing problem-solving strategies.